Isolation of Cellulolytic Bacteria from Kalkun (Meleagris gallopavo) Gastro-Intestinal Tract as a Candidate Probiotics for Poultry - Muh. Aidil Fitriyan Fadjar Suryadi; Muhammad Hipzul Mursyid; Khairil Anwar; Muhamad Ali; Djoko Kisworo (Jurnal Penelitian Pendidikan IPA, 2023)
This study has been conducted to isolate and identify cellulolytic bacteria from the digestive tract of turkeys (Meleagris gallopavo) as probiotic candidates for poultry. This study has obtained 4 bacteria that have the potential as probiotic candidates through the morphological identification stage, the ability to produce cellulase enzymes and resistance to acidic pH conditions. The test found that RDL code bacteria bacteria have the highest ability to produce enzyme cellulase characterized by the formation of a clearing zone with a diameter of 11 mm, the second highest PVB2 code bacteria with a clearing zone diameter of 7 mm, DB1 4 mm, and RSL 2 mm and the results of bacterial viability tests isolated at low pH (2.0) showed the highest viability after incubating for 4 hours. RDL viability is 65%, RSL 48%, DB1 50%, and PVb2 29%. So based on the tests that have been carried out, it is estimated that the 4 bacteria are candidates for Lactobacillus sp. worthy to be used as a probiotic for poultry